1973
DOI: 10.1080/03015521.1973.10427925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium fertiliser., soil magnesium status, and soil type on uptake of magnesium by pasture plants from magnesium fertilisers

Abstract: Comparisons were made between low rates of dolomite (D) and superphosphate (SP) applied separately or in a dry mixture (SP + D), dolomite-'"reverted" superphosphate (DSP), serpentine-reverted superphosphate (SSP), superphosphate plus ground serpentine rock (SR), and superphosphate plus calcined magnesite (MgO), supplying 27.5 to 55 kg total Mg/ha, in the presence and absence of K fertilise'r, as sources of Mg for uptake by pasture plants in 23 experiments on a range of soil types (pH 5.2 to 6.6) of variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1978
1978
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…A decrease in plant Mg concentrations resulting from liming has also been measured in other experiments (McNaught et al 1968(McNaught et al , 1973a but the present results suggest the cause. Overall, the decrease in Mg concentration in the grass was proportional to the increase in yield (see Table 2) resulting in no change in Mg uptake.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A decrease in plant Mg concentrations resulting from liming has also been measured in other experiments (McNaught et al 1968(McNaught et al , 1973a but the present results suggest the cause. Overall, the decrease in Mg concentration in the grass was proportional to the increase in yield (see Table 2) resulting in no change in Mg uptake.…”
Section: Discussionsupporting
confidence: 84%
“…This was associated with a decrease in herbage Mg; an effect which has been observed in other field trials (McNaught et al 1968(McNaught et al , 1973a.…”
Section: Introducnonsupporting
confidence: 73%
“…The effect of rate of K fertiliser application on pasture uptake of other cations has been reported by McNaught et al (1973) and Morton et al (2000) and the effect of dairy effluent application on pasture by Bolan et al (2000). Goff & Horst (1997) reported that addition of K to pre-calving rations for dairy cows fed indoors increased the incidence of hypocalcaemia.…”
Section: Introductionmentioning
confidence: 77%
“…The reduction in herbage magnesium concentrations caused by adding magnesium to both the high magnesium selection and the Nui controls is almost certainly a Steenbjerg effect (Steenbjerg 1951) and does not affect the argument for genetic control. Genetic control of magnesium concentration in ryegrass may help to explain the generally poor results, in terms of tissue magnesium, when magnesium salts are applied to pasture (McNaught et al 1968(McNaught et al , 1973.…”
Section: Magnesium Levels Of Plants Grown In Egmont Soilmentioning
confidence: 99%